The Role of Exosomal microRNA in Cancer Drug Resistance - Guo, Qiao-ru; Wang, Hui; Yan, Ying-da; Liu, Yun; Su, Chao-yue; Chen, Hu-biao; Yan, Yan-yan; Adhikari, Rameshwar; Wu, Qiang; Zhang, Jian-ye (Frontiers in Oncology, 2020)
Exosomes have a great influence on initiation and progression of cancer. In the tumor microenvironment, not only cancer cells, but fibroblasts and immunocytes can secrete exosomes. Exosomes act as a communicator between cells by transferring different cargos and microRNA (miRNA) is one of the cargos that exosomes transfer. In the course of cancer treatment, drug resistance is an important factor that affects therapeutic effect. Many studies have shown that miRNA carried by exosomes is closely related to the development of drug resistance. This article will introduce the mechanism of drug resistance which is related to the exosomal miRNA.